Study of feto-maternal outcome in patients with intra uterine fetal death - Thaker, Rajal V.; Munshi, Kavina S.; Patel, Vivek A.; Vasava, Dipti C.; Makwana, Nilesh M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intra Uterine Fetal Death (IUFD) is an important issue in modern obstetrics. This study has been undertaken to find out the incidence of IUFD, socio-demographic factors, probable etiological factors, mode of delivery, its outcome and complications if any. Methods: This retrospective observational study was carried out at a tertiary care hospital. Data was collected from case papers of patients who have delivered beyond 20 weeks and/or baby weighing more than 500 grams and having IUFD prior to onset of labor or during labor with singleton pregnancy. Results: Incidence of IUFD was 17.2 per 1000 births. Majority of the patients 93 (48.1%) were in age group of 26-30 years, 115 (59.5%) came as an emergency and 94 (48.7%) were primi gravida. Majority 89 (46.1%) patients had not taken any antenatal visit. IUFD occurred due to unexplained etiology, pre-eclampsia-eclampsia, anemia, uncontrolled diabetes, jaundice, antepartum haemorrhage and congenital malformation in 77 (39.9%), 51 (26.4%), 10 (5.1%), 7 (3.6%), 4 (2%), 29 (15%) and 2 (1%) respectively. Vaginal delivery occurred in 151 (78.2%). Majority of dead babies 111 (57.5%) were male, 71 (36.7%) were weighing 1kg or less and 92 (47.6%) were macerated. Emotional upset, DIC, PPH and ARF occurred in 193 (100%), 21 (10.8%), 15 (7.7%) and 1 (0.5%) respectively. Conclusions: Majority of patients were unregistered and had not taken antenatal care or had inadequate antenatal care. Pre-eclampsia-eclampsia, APH, anemia and diabetes were the leading cause of IUFD along with unknown causes. A significant proportion of IUFD can be prevented by health education regarding adequate antenatal care, warning signs and institutional deliveries.